PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP KINERJA LINGKUNGAN - Widarsono, Agus; Putri Hadiyanti, Cantika (Program Studi Akuntansi FPEB UPI, 2015)
This study aims to test and obtain empirical evidence of factors that affect the environmental performance partially and simultaneously. Factors studied in this research are profitability, leverage and liquidity. The research method used is descriptive method verifikatif. With verificative testing using multiple regression, partial test (t test) and simultaneous test (F test). The data used are secondary data that is the company's annual report and PROPER report of Ministry of Environment as sample in the research. The sample of research is 11 State-Owned Enterprise (BUMN) Year 2009-2013 taken by using purposive sampling method. The results of this study indicate that profitability, leverage and liquidity have no significant effect on environmental performance partially. And profitability, leverage, and profitability have no significant effect on environmental performance simultaneously.